Effectiveness of Open Inquiry Instructional Strategy on Secondary School Chemistry Students’ Conceptual Knowledge - Omolabake Temilade Ojo; Bamidele Emmanuel Tijani (Journal of Research in Environmental and Science Education, 2025)
Chemistry is a cornerstone of science, yet students in Nigeria often face challenges in achieving conceptual understanding due to the reliance on traditional teaching methods. These methods prioritise rote memorisation over deep comprehension, limiting students’ ability to apply scientific principles effectively. To address this challenge, this study investigates the impact of the open inquiry instructional strategy in enhancing secondary school students’ conceptual knowledge in chemistry. Using a quasi-experimental pre-test-post-test design, 322 Senior Secondary School 1 (SSS 1) students from six purposively selected schools participated in the study. The experimental group (166 students) was taught using open inquiry while the control group (156 students) received demonstration-based instruction. Data were collected using the Two-Tier Diagnostic Test (TTDT), assessing students’ ability to explain concepts, make connections, and apply scientific reasoning. Paired samples t-tests and ANCOVA were employed for data analysis. The findings revealed that students taught with open inquiry demonstrated significantly higher conceptual knowledge than those taught with the demonstration method. Notably, no significant differences were observed in outcomes between public and private school students, indicating the strategy’s adaptability across different educational contexts. These findings contribute to the growing body of knowledge on effective instructional strategies for teaching chemistry in senior secondary schools and highlight the importance of integrating open inquiry into science curricula. The study recommends the incorporation of inquiry-based teaching approaches alongside adequate teacher training to enhance students’ learning experiences. Future research should explore the long-term impact of open inquiry and its effectiveness in other scientific disciplines.